A superlinearly convergent ODE-type trust region algorithm for nonsmooth nonlinear equations - Yigui, Ou (Journal of applied mathematics & computing, 2006)
This paper presents a new trust region algorithm for solving nonsmooth nonlinear equation problems which posses the smooth plus non-smooth decomposition. At each iteration, this method obtains a trial step by solving a system of linear equations, hence avoiding the need for solving a quadratic programming subproblem with a trust region bound. From a computational point of view, this approach may reduce computational effort and hence improve computational efficiency. Furthermore, it is proved under appropriate assumptions that this algorithm is globally and locally super-linearly convergent. Some numerical examples are reported.[PUBLICATION ABSTRACT]